Intervening Effect of Tripartite Consultation On the Performance of State Corporations in Kenya - Nzioki, Susan (International Journal of Economics, Commerce and Management, 2015)
The study sought to establish the intervening effect of tripartite consultation between the role of social partners, the tripartite consultation system, the economic change issues, the relationship between social partners and performance of state corporations in Kenya. The study was carried out in Nairobi County in Kenya and it involved 279 both unionized and non-unionized employees of state corporations in the County. A descriptive survey design was used. A structured questionnaire with Likert scale questions and an interview guide were used to collect data from the selected subjects. The study applied the Industrial Relations model envisaged by Dunlop, which was believed to reflect the existing tripartite consultation arrangements. Data was analysed quantitatively and qualitatively using Statistical Package of Social Sciences (SPSS). The study found that tripartite consultation had intervened positively between the stated variables and performance of state corporations. Tripartite consultation had helped to; gather views and advice of employers’ and workers’ representatives, prepare labour laws, establish national bodies responsible for employment, elaborate and implement of economic and social development plans. The study recommends that the social partners should collectively strengthen and adhere to the established tripartite consultation framework in order to enhance industrial peace. The findings will help the social actors to collectively consult in good faith for industrial harmony and national development.
Keywords: Tripartite consultation; Intervening effect; Social actors; Industrial peace; Performance